2022
DOI: 10.1021/acs.analchem.2c00763
|View full text |Cite
|
Sign up to set email alerts
|

Boron and Nitrogen-Codoped Carbon Dots as Highly Efficient Electrochemiluminescence Emitters for Ultrasensitive Detection of Hepatitis B Virus DNA

Abstract: In this work, boron and nitrogen-codoped carbon dots (BN-CDs) as highly efficient electrochemiluminescence (ECL) emitters with advantages of low excitation potential and high ECL efficiency were prepared to establish a novel ternary ECL system for ultrasensitive detection of HBV-DNA. Especially, both platinum nanoflowers (Pt NFs) and boron radicals (B • ) from the BN-CDs could accelerate the reduction of coreactant S 2 O 8 2− to abundant SO 4•− simultaneously, making the BN-CDs have outstanding ECL performance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 36 publications
2
27
0
Order By: Relevance
“…In addition, the efficiency of ECL is also affected by many factors, such as electrode material, co-reactant, imaging buffer, electrolyte, and so on. To enhance the detection and imaging contrast of ECL, the following improvements are under development: the common strategy for positive labeling detection is to synthesize brighter dyes and the enrichment and cascade amplification of luminescent probes or co-reactants such as ECL systems based on quantum dots , (see Figure C), porous materials, single-atom catalyst, carbon-based materials, and the rational design of co-reactants. In addition to the designing of novel ECL probes and co-reactant, the electrode applied in the ECL reaction is an important part of the ECL imaging system, which can also be improved . As a new type of semiconductor electrode, the boron-doped diamond electrode (BDDE) has a good redox window in aqueous solution, which can avoid the side reaction of water electrolysis on ECL .…”
Section: Improvements Of Ecl Imagingmentioning
confidence: 99%
“…In addition, the efficiency of ECL is also affected by many factors, such as electrode material, co-reactant, imaging buffer, electrolyte, and so on. To enhance the detection and imaging contrast of ECL, the following improvements are under development: the common strategy for positive labeling detection is to synthesize brighter dyes and the enrichment and cascade amplification of luminescent probes or co-reactants such as ECL systems based on quantum dots , (see Figure C), porous materials, single-atom catalyst, carbon-based materials, and the rational design of co-reactants. In addition to the designing of novel ECL probes and co-reactant, the electrode applied in the ECL reaction is an important part of the ECL imaging system, which can also be improved . As a new type of semiconductor electrode, the boron-doped diamond electrode (BDDE) has a good redox window in aqueous solution, which can avoid the side reaction of water electrolysis on ECL .…”
Section: Improvements Of Ecl Imagingmentioning
confidence: 99%
“…The experiment results suggested that THz spectroscopy measurements of HBV DNA by GMNPs-RCA-AuNPs sandwich assay integrated with the MM biosensor chip provided a new alternative method for early diagnosis and treatment of HBV. A recent study revealed that the highly efficient electrochemiluminescence (ECL) biosensor could realize the ultrasensitive detection of HBV DNA from 100 aM to 1 nM while the limit of detection was 18.08 aM (Guo et al, 2022). The more suitable metamaterials and better signal amplification strategies would be considered to further improve sensitivity of THz biosensor in the future study.…”
Section: Sensitivity Of Terahertz Biosensing Strategy For Hepatitis B...mentioning
confidence: 99%
“…In addition, quantification of viral nucleic acids can be utilized in the early diagnosis, treatment, and assessment of how an individual is responding to antiviral therapy (Amini et al, 2017;Hsieh et al, 2022a). There is an urgent need to produce a diagnostic device, such as biosensing for infectious samples detection, which can carry out rapid, sensitive, and accurate detection of viral infection and replication during its early stages (Moitra et al, 2021;Hsieh et al, 2022b;Guo et al, 2022;Dighe et al, 2022;Liang et al, 2022;Moitra et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…And ECL is considered to be a promising assay method for determination of CoVNP owing to its advantages of low background signals, high sensitivity, simple equipment and electrochemical controllability [ [21] , [22] , [23] , [24] ]. This advanced technology has been successfully applied in many researched fields including biomarkers detection [ 25 ], bio-imaging [ 26 ], point-of-care diagnosis [ 27 ], as well as DNA and proteins detection [ 28 , 29 ]. In particular, tris (2,2′-bipyridine) ruthenium (II) (Ru(bpy) 3 2+ ) and its derivatives have acted as ECL reagents on ECL sensors for long time because of their high ECL efficiency.…”
Section: Introductionmentioning
confidence: 99%